Capital regulation, liquidity requirements and taxation in a dynamic model of banking - Gianni De Nicolò; Andrea Gamba; Marcella Luccetta (Deutsche Bundesbank, 2012)
This paper studies the impact of bank regulation and taxation in a dynamic model where banks are exposed to credit and liquidity risk and can resolve financial distress in three costly forms: bond issuance, equity issuance or fire sales. We find an inverted U-shaped relationship between capital requirements and bank lending, efficiency, and welfare, with their benefits turning into costs beyond a certain threshold. By contrast, liquidity requirements reduce lending, efficiency and welfare significantly. On taxation, corporate income taxes generate higher government revenues and entail lower efficiency and welfare costs than taxes on non-deposit liabilities.
Keywords: G21; G28; G33; 330; Bank Regulation; Taxation; Dynamic Banking Model